1981
DOI: 10.1001/jama.1981.03310260024022
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function After Mantle Irradiation in Hodgkin's Disease

Abstract: We studied the thyroid function of 64 patients with Hodgkin's disease who received mantle irradiation during the period 1966 to 1976. More than two thirds (44 of 64) had some thyroid dysfunction. Twenty had mild dysfunction manifested by an abnormal thyroid-stimulating hormone response to thyrotropin-releasing hormone. Twenty had what could be termed compensated hypothyroidism while four were overtly hypothyroid. The severity of dysfunction was not related to age, sex, or chemotherapy. We found, however, that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…They attributed this apparent paradox to the lymphangiogram performed before irradiation in the lymphoma patients. The studies from several other groups (Shalet et al, 1977;Smith et al, 1981) have supported the suggestion made by the Stanford workers but others have found equivalent rates of thyroid dysfunction regardless of whether lymphangiography preceded radiation therapy (Tamura et a!., 1981).…”
Section: Radiation-induced Thyroid Dysfunctionsupporting
confidence: 53%
See 1 more Smart Citation
“…They attributed this apparent paradox to the lymphangiogram performed before irradiation in the lymphoma patients. The studies from several other groups (Shalet et al, 1977;Smith et al, 1981) have supported the suggestion made by the Stanford workers but others have found equivalent rates of thyroid dysfunction regardless of whether lymphangiography preceded radiation therapy (Tamura et a!., 1981).…”
Section: Radiation-induced Thyroid Dysfunctionsupporting
confidence: 53%
“…The dose of irradiation to the neck received by the patients studied by these two groups ranged between 4000 to 5000 cGy over four to five weeks. Not unexpectedly the incidence and severity of radiation-induced thyroid dysfunction appears to be lower in patients receiving less than 4000 cGy to the neck (Smith et al, 1981). The inclusion of a TRH stimulation test to amplify minor abnormalities in basal TSH secretion has revealed a further group of patients who show an exaggerated TSH response to TRH but normal basal serum TSH, T3 and T4 concentrations (Smith et al, 1981;Shalet et al, 1977).…”
Section: Radiation-induced Thyroid Dysfunctionmentioning
confidence: 99%
“…In two large investigations ( 5 , 8) about 20 per cent of the patients had low S-T4 and elevated S-TSH levels, indicating biochemical hypothyroidism, and in addition about 40 per cent of the cases had an elevated S-TSH level indicating subclinical hypothyroidism after irradiation with 40 to 50 Gy to the neck in 4 to 5 weeks. A TRH stimulation test has revealed another group of patients with normal S-T4 and S-TSH values but an exaggerated S-TSH response to TRH (10).…”
Section: Discussionmentioning
confidence: 99%
“…Radiation-induced primary hypothyroidism has been reported to occur rather frequently after mantle irradiation in Hodgkin's disease (10) and following treatment of head and neck cancer (12). In view of these reports and of the occasional observation of breast cancer patients with primary hypothyroidism at this hospital, an investigation was carried out on the effect on thyroid function of postoperative radiation therapy following mastectomy, and the results are now presented.…”
mentioning
confidence: 98%
“…Although an increased incidence of hypothyroidism has been reported in breast cancer patients (Mittra & Hayward, 1974;Rose & Davies, 1978;Thomas et al, 1983) other workers have not observed such an association (Schottenfield, 1968;Hedley et al, 1981). Radiotherapy involving the thyroid region for head and neck cancer (Shafer et al, 1975;Posner et al, 1984) or Hodgkin's disease (Schimpff et al, 1980;Smith et al, 1981;Peden et al, 1982) has been reported to be followed by an increased incidence of mostly subclinical hypothyroidism. In these cases the whole thyroid was generally irradiated with cumulative doses ranging from 40 to 70Gy.…”
mentioning
confidence: 99%